Electrochemical Magnetoimmunosensor for Progesterone Receptor Determination. Application to the Simultaneous Detection of Estrogen and Progesterone Breast‐cancer Related Receptors in Raw Cell Lysates. Issue 8 (10th December 2015) - Eletxigerra, U.; Martinez‐Perdiguero, J.; Merino, S.; Barderas, R.; Ruiz‐Valdepeñas Montiel, V.; Villalonga, R.; Pingarrón, J. M.; Campuzano, S.
Abstract: An electrochemical magnetoimmunosensor for the determination of progesterone receptor (PR) making use of functionalized magnetic microbeads (MBs), a sandwich‐type immunoassay and amperometric detection at disposable screen‐printed carbon electrodes (SPCEs) was described for the first time in this work. This selective and sensitive magnetoimmunosensor, with a detection limit of 22 pg mL −1, was successfully applied to the determination of PR in raw cell lysates with just a dilution as sample treatment and exhibiting no matrix effect. The advantageous performance in terms of simplicity and assay time over commercial ELISAs makes it competitive with conventional strategies providing rapidly quantitative and reliable results on this biomarker currently used in the clinical practice for diagnosis, follow‐up and monitoring of metastatic breast cancer. In addition, a dual magnetoimmunosensor using screen‐printed dual carbon electrode (SPdCE) has been implemented for the simultaneous determination of PR and estrogen receptor α (ERα) in cell lysates. This dual receptor determination allows a more accurate diagnosis enabling a more efficient treatment. The usefulness of this dual magnetoimmunosensing platform was demonstrated by discriminating raw lysates of two types of cancer cells (MCF‐7 and MDA‐MB‐436) with significantly different PR/ERα expression levels. Abstract :